2017
DOI: 10.12816/0045782
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cost Efficiency of Islamic Banks of Pakistan

Abstract: Efficient utilization of the resources as trust of the depositors is the first and foremost responsibility of the Islamic bank, as directed in . Efficiency in managing the cost of the bank is only aspect that bank can control which can lead to increase in income of bank and depositors. There is a vast literature on theoretical models of business cost minimization but in reality the situation is not promising. This paper aims to measure and compare the real cost efficiency of full-fledged Islamic banks operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The data from Bank Negara Malaysia shows that Islamic banking has just penetrated less than 25 percent of the total banking asset. Thus, the continued development of the Islamic financial system depends on the quality of the services and fulfilling the criterion set by customers in order to tackle their good perception towards Islamic financial system (Haron et al, 1994;Yousuff, 2006;Sadiq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The data from Bank Negara Malaysia shows that Islamic banking has just penetrated less than 25 percent of the total banking asset. Thus, the continued development of the Islamic financial system depends on the quality of the services and fulfilling the criterion set by customers in order to tackle their good perception towards Islamic financial system (Haron et al, 1994;Yousuff, 2006;Sadiq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This leads us to the finding that Islamic banks also receive affect from variations in interest rates. Sadiq et al (2017) find that Islamic banks in Pakistan are less cost efficient due to excess liquidity, inadequate support and competition from conventional banks. Addressing the financial sector of Pakistan using DEA technique in another study it has been found that insurance sector in Pakistan is more technically efficient than banking sector (Shah and Masood, 2017).…”
Section: Literature Review Literature On Islamic Banksmentioning
confidence: 98%
“…This leads to the finding that Islamic banks also receive effect from variations in interest rates. Sadiq et al (2017) and Shah and Masood (2017) find that Islamic banks in Pakistan are less cost efficient because of excess liquidity, inadequate support and cut throat competition from conventional banks. Hamza and Saadaoui (2018) in their work on Islamic banks report that changes in interest rates negatively affect financing of Islamic banks.…”
Section: Risk Management In Islamic Banksmentioning
confidence: 99%